Hepatocellular Carcinoma and Obesity, Type 2 Diabetes Mellitus, Cardiovascular Disease: Causing Factors, Molecular Links, and Treatment Options - Zhang, Chunye; Liu, Shuai; Yang, Ming (Frontiers in Endocrinology, 2021)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, which will affect more than a million people by the year 2025. However, current treatment options have limited benefits. Nonalcoholic fatty liver disease (NAFLD) is the fastest growing factor that causes HCC in western countries, including the United States. In addition, NAFLD co-morbidities including obesity, type 2 diabetes mellitus (T2DM), and cardiovascular diseases (CVDs) promote HCC development. Alteration of metabolites and inflammation in the tumor microenvironment plays a pivotal role in HCC progression. However, the underlying molecular mechanisms are still not totally clear. Herein, in this review, we explored the latest molecules that are involved in obesity, T2DM, and CVDs-mediated progression of HCC, as they share some common pathologic features. Meanwhile, several therapeutic options by targeting these key factors and molecules were discussed for HCC treatment. Overall, obesity, T2DM, and CVDs as chronic metabolic disease factors are tightly implicated in the development of HCC and its progression. Molecules and factors involved in these NAFLD comorbidities are potential therapeutic targets for HCC treatment.